Morphology and ultrastructure of Siberian sturgeon (Acipenser baerii) spermatozoa using scanning and transmission electron microscopy - Psenicka, Martin; Alavi, S M Hadi; Rodina, Marek; Gela, David; Nebesarova, Jana; Linhart, Otomar (Biology of the cell, 2007)
BACKGROUND INFORMATION: Available data concerning the sperm morphology of teleost fishes demonstrate wide variation. In the present study, the spermatozoa of Siberian sturgeon (Acipenser baerii Brandt, 1869), a chondrostean fish, was investigated. In contrast with teleost fish, chondrostean spermatozoa have a head with a distinct acrosome, whereas other structures, such as a midpiece and a single flagellum, are present in spermatozoa of most species. RESULTS: The average length of the head including the acrosome and the midpiece was 7.01+/-0.83 microm. Ten posterolateral projections derived from the acrosome were present on a subacrosomal region, with mean lengths of 0.94+/-0.15 microm and widths of 0.93+/-0.11 microm. The nucleus consisted of electrodense homogeneous nuclear chromatin. Three intertwining endonuclear canals, bound by membranes, traversed the nucleus longitudinally from the acrosomal end to the basal nuclear fossa region. There were between three and six mitochondria, two types of centrioles (proximal and distal) in the midpiece and two vacuoles composed of lipid droplets. The flagellum (44.75+/-4.93 microm in length), originating from the centriolar apparatus, had a typical 9+2 eukaryotic flagellar organization. In addition, there was an extracellular cytoplasm canal between the cytoplasmic sheath and the flagellum. CONCLUSIONS: A principal components analysis explained the individual morphological variation fairly well. Of the total accumulated variance, 41.45% was accounted for by parameters related to the head and midpiece of the sperm and the length of the flagellum. Comparing the present study with previous studies of morphology of sturgeon spermatozoa, there were large inter- or intra-specific differences that could be valuable taxonomically.
Keywords: Male; akrozom; Cell Nucleus; Flagella; Spermatozoa; mužské pohlaví; buněčné jádro; analýza hlavních komponent; flagella; ryby; Principal Component Analysis; Acrosome; Fishes; Animals; Microscopy, Electron, Transmission; Microscopy, Electron, Scanning; zvířata; spojovací oddíl spermie; spermie; Sperm Midpiece; mikroskopie elektronová rastrovací; transmisní elektronová mikroskopie